Relationship Between e-Health Literacy and Psychosocial Stress Levels in Adolescents - Sonia Pransiska; Misrawati Misrawati; Wice Purwani Suci (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
E-health literacy has positive and negative impacts. The positive impact of e-health literacy can be considered as a guardian of mental health, especially stress. While the negative impact is that the activity of seeking health information can lead to self-diagnosis which can have an impact on behavior, namely triggering anxiety and even stress. The purpose of this study was to determine the relationship between e-health literacy and the level of psychosocial stress in adolescents. The design used is descriptive correlation and cross sectional approach. The research sample was 276 adolescents using a stratified random sampling technique. The analysis used is the chi-square test. The results showed that there were 261 people with a good level of e-health literacy (94.6%), as many as 101 people had a moderate level of psychosocial stress (36.6%). Based on statistical tests, there was no relationship between e-health literacy and stress levels. psychosocial in adolescents with p value (0.950) alpha (0.05). Based on the results obtained, it is recommended for future researchers to intervene in adolescents who experience moderate to severe psychosocial stress